Hubungan Gaya Hidup Hedonis Dengan Kecenderungan Impulsive Buying Pada Remaja - Haryani, Siti Dinda; Syaf, Auliya; Fadhli, Muhammad (ANFUSINA: Journal of Psychology, 2022)
Impulsive buying is an irrational purchase that occurs quickly without any consideration and there is no process of searching for information about the product purchased so that the purchase occurs because of an emotional impulsive. One of the factors that influence impulsive buying is a hedonic lifestyle. The hedonic lifestyle is a lifestyle or lifestyle that is expressed with activities, interests and opinions that prioritize emotional properties rather than logic and is a lifestyle that leads to pleasure which is the goal of life. This study aims to determine the relationship between hedonic lifestyle and impulsive buying in adolescents. This study uses a quantitative method with Pearson's product moment analysis. The subjects in this study were 360 adolescents aged 12-23 years in the city of Pekanbaru which were taken using quota sampling. Based on the results of research conducted that there is a positive relationship between the hedonic lifestyle and the impulsive buying tendency of teenagers in the city of Pekanbaru with a significance value of 0.000 and a correlation coefficient of 0.735, which means the higher the hedonic lifestyle, the higher the tendency of impulsive buying in adolescents, and conversely the lower the hedonic lifestyle. hedonic lifestyle, the lower the tendency of impulsive buying in adolescents in Pekanbaru. Thus, the hedonic lifestyle carried out by teenagers in Pekanbaru has a relationship with the tendency of impulsive buying.Keywords: Impulsive Buying, Hedonic Lifestyle, Teenagers